2022
DOI: 10.1371/journal.pone.0277031
|View full text |Cite
|
Sign up to set email alerts
|

Agreement and relationship between measures of absolute and relative intensity during walking: A systematic review with meta-regression

Abstract: Introduction A metabolic equivalent (MET) is one of the most common methods used to objectively quantify physical activity intensity. Although the MET provides an ‘objective’ measure, it does not account for inter-individual differences in cardiorespiratory fitness. In contrast, ‘relative’ measures of physical activity intensity, such as heart rate reserve (HRR), do account for cardiorespiratory fitness. The purpose of this systematic review with meta-regression was to compare measures of absolute and relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 69 publications
3
7
0
Order By: Relevance
“…In keeping with this, we observed higher METs (~7) when exercising (walking) at the same relative intensity in the trained PMW and untrained PreM groups compared to the untrained PMW (~5METs), suggesting higher absolute exercise intensity in the trained PMW and untrained PreM groups compared to the untrained PMW. Lack of agreement between relative and absolute exercise intensities, particularly with walking, as employed in the current study, has been previously reported 40 . The effects of relative versus absolute exercise intensity on vascular function in PMW remain to be determined and warrant further research.…”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…In keeping with this, we observed higher METs (~7) when exercising (walking) at the same relative intensity in the trained PMW and untrained PreM groups compared to the untrained PMW (~5METs), suggesting higher absolute exercise intensity in the trained PMW and untrained PreM groups compared to the untrained PMW. Lack of agreement between relative and absolute exercise intensities, particularly with walking, as employed in the current study, has been previously reported 40 . The effects of relative versus absolute exercise intensity on vascular function in PMW remain to be determined and warrant further research.…”
Section: Discussionmentioning
confidence: 50%
“…Our study compared vascular function in trained and untrained women using a prescribed exercise stimulus that was relative to the individuals' cardiorespiratory fitness (i.e., the same relative exercise intensity). While this individualized approach is commonly used for the assessment, monitoring, and enhancement of cardiorespiratory fitness, 40 it is appropriate to acknowledge that exercising at a relative intensity may result in differing absolute metabolic (e.g., a metabolic equivalent [MET]) and/or cardiovascular (e.g., HR) strain, particularly when comparing trained versus untrained individuals. A MET is a common method used to objectively quantify physical activity intensity, using a ratio of the metabolic cost produced by different types of exercise and intensity compared to the metabolic cost of sitting quietly (e.g., 3.5 mL/kg/min).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations